Coronary Artery Hematoma Treated with Fenestration Using a Novel NSE Alpha® Scoring Balloon - Naohiro Funayama; Takao Konishi; Tadashi Yamamoto; Daisuke Hotta (Case Reports in Cardiology)
The optimal management of coronary intramural hematoma has not been defined. We described a case in which coronary occlusion developed due to an intramural hematoma after percutaneous coronary intervention for mid left circumflex artery (LCX). Intravascular ultrasound (IVUS) demonstrated the progression of the intramural hematoma and a totally compressed true lumen. Our approach was based on fenestration with a scoring balloon (NSE Alpha, Goodman, Japan), which allowed the deployment of an additional stent to be avoided. In conclusion, this management can be effectively and safely performed.